Acquiring preferred mode of aggregation through positional antagonism for saponification triggered gelation. (8th March 2023) - Chand, Prem; Kumar, Ashish
Abstract : The mode of aggregation during saponification triggered gelation depends on the positional occupancy of a substituent (–OCH3 group). Abstract : A substituent mediated change in the mode of aggregation during saponification triggered transformation of two ester-containing Zn II -complexes (A–B ) into metallogels (MGA –MGB ) has been presented. Structures of A and B have been inspired by reported complexes 1 and C4, which exhibited gelation via the saponification triggered method. A consists of an additional –OCH3 group compared to 1, while B and C4 are structural isomers, i.e., identical except one positionally altered –OCH3 . During gelation, 1 and C4 exhibited 'J-aggregation', but herein, in similar conditions, A and B significantly acquire 'H-aggregation', leading to the formation of metallogels. This discrepancy has been addressed for the first time, which signified that gelators with isomeric dissimilarity acquired different modes of aggregation toward gelation. A distinguishing role of particular substituents has been revealed for a suitable mode of aggregation for this class of gelation, which is designated as 'positional antagonism'. This has been susbtantiated by UV-vis, fluorescence, and 1 H-NMR spectroscopy as well as AFM, SEM, rheological, and DFT studies.